Design of a bactericidal hydrogel scaffold containing genipin crosslinked HF-18 peptide - Boncukcu, Nilbeste; Akgul, Busra; Akmayan, Ilkgul; Berber, Hale; Abamor, Emrah Sefik; Ozbek, Tulin; Derman, Serap (WILEY, 2023)
Wound healing is a process getting affected by internal and external factors and might be interrupted by infections. To overcome infections during wound healing, novel antibacterial agents such as antimicrobial peptides have gained popularity because of the rising antibiotic resistance. Therefore, in this study, a three-dimensional polymeric scaffold was designed for the controlled release of HF-18 peptide, with the contribution of hyaluronic acid, chondroitin sulfate, and chitosan polymers with the crosslinker genipin. The obtained scaffold structure (OPT) was found to have interconnected pores, was pH-responsive and swelled more in acidic conditions (5446.5% at pH: 5.0). It was observed that HF-18-loaded OPT (P-OPT) was able to release HF-18 peptide both in acidic and neutral conditions in a controlled release manner. This study also demonstrated that both OPT and P-OPT were biocompatible and promoted L929 cell attachment and migration. Antimicrobial activity assessments demonstrated that P-OPT was effectively bactericidal on Staphylococcus aureus and methicillin-resistant S. aureus. Moreover, OPT produced a synergistic effect on the antimicrobial activity of HF-18 peptide, as P-OPT showed activity below the reported MIC value. As a result, OPT is considered a promising scaffold as a carrier for HF-18 for wound healing.
Keywords: antimicrobial peptides; HF-18; hydrogel; polymeric scaffold; wound healing; HYALURONIC-ACID; CHONDROITIN SULFATE; CHITOSAN HYDROGELS; GELATIN SCAFFOLDS; BEHAVIOR; LINKING; GROWTH; PH; Biotechnology & Applied Microbiology; Food Science & Technology